A Case Study Analysis of Clt Methods to Develop Grammar Competency for Academic Writing Purposes at Tertiary Level - Asmani, Almodad Biduk (Humaniora, 2013)
The purpose of the research project is to find out how effective grammar teaching and learning using the Principled CLT method can improve the ability of freshman Binus University students to understand and use grammar knowledge for academic writing purposes. The research project is expected to result in computer-animated format which can be used as one of the main tools in teaching and learning grammar at tertiary level. The research project applies the descriptive quantitative approach, and thus uses numeric data. The research project involves two subject groups, which are experimental and control. The two groups are pre-tested so as to find out their level of grammar competency by their academic writing works. The experimental group receives the treatment of grammar learning by using the Principled CLT approach, while the control group receives the standard CLT approach. Then, the two groups have the post-test, and the results are compared. Through statistics, the numerical data show that there is no significant difference between the two methods? results, and as a result, either method has its own strength and weaknesses. If one is to be implemented, it must be linked to the specific goals and purposes that each entails.